Analisis Akuntansi Kombinasi Bisnis Dengan Konvergensi IFRS Pada Laporan Keuangan Perusahaan - Muhamad Riswantoro; Wisnu Pramudya; Ahmad Danu; Endang Kartini Panggiarti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
In today's competitive business environment, there are many companies that look like a single entity when in fact they are made up of several separate companies. Some of these companies conduct business combinations consisting of mergers, acquisitions, and consolidations. In conducting these business combinations, there are regulations that govern, namely PSAK 22 as a result of IFRS convergence. This study aims to further analyze business combinations with IFRS convergence. The research method used is a quantitative engineering approach by focusing on literature review. The results of this study indicate a change in the purchase method to goodwill impairment testing, adjustments to non-controlling interests, and more detailed disclosures.